Fever : its biology, evolution, and function - Kluger, Matthew J., 1946- (Princeton University Press, 1979)
Fever has long been recognized as a symptom of disease. Until the past century it was considered a healthy sign; since then this view has changed and the use of drugs to reduce fever has grown quite common. Acting on the revival of interest as to whether the effects of fever are beneficial or harmful, Matthew Kluger and other physiologists began a series of experiments designed to resolve this question. This book synthesizes their research, making a case not only for the beneficial function of fever but also for the re-evaluation of current clinical practices regarding fever. Originally published in 1979. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Keywords: Fever.; Body temperature -- Regulation.; Infection.; Physiology, Comparative.; Fever; Body Temperature Regulation; Infections.; Physiology, Comparative; Fièvre.; Thermorégulation.; Physiologie comparée.; MEDICAL -- Diseases.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Clinical Medicine.; MEDICAL -- Evidence-Based Medicine.; MEDICAL -- Internal Medicine.; Body temperature -- Regulation; Infection